Perception of malaria and cultural diversity of antimalarial plants in three sympatric communities: Agni, Akyé and Gwa in the District of Alépé, Côte d’Ivoire (Asian Journal of Ethnobiology, 2022)
Abstract. Diop AL, Malan DF, Kougbo MD. 2022. Perception of malaria and cultural diversity of antimalarial plants in three sympatric communities: Agni, Akyé and Gwa in the District of Alépé, Côte d’Ivoire. Asian J Ethnobiol 5: 1-11. Each ethnic group has developed its own culture expressed through traditional health care systems. This study aimed to determine how the communities with different histories perceive and manage malaria, a disease with a high prevalence rate in the Sub-Saharan region. An ethnobotanical survey was carried out in 10 Agni, Akyé and Gwa communities villages. Two surveys were conducted: a house-to-house survey based on free lists interviews and an individual walk-in-the-woods interview. Frequency of quotation and Smith’s index was used to assess antimalarial plants’ knowledge level. The Venn diagram, hierarchical clustering, and Spearman correlation test compared malaria perception and the antimalarial plants among the three communities. In the studied communities, six forms of malaria were recognized with various symptoms. Seventy-seven antimalarial plants were used to cure these forms. The proportion of antimalarial plants specific to each community was quite low. This study has revealed the differences and similarities between the antimalarial plants used by the communities living in the same geographical area. This study has also highlighted new plants in the study area that could treat malaria. Finally, awareness must be made in the studied communities on different forms of malaria for a better understanding of this disease.
Keywords: Alépé, Alstonia boonei, Annickia polycarpa, Côte d'Ivoire, malaria, medicinal plants